1986
DOI: 10.1159/000284448
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Some Symptoms in Adolescence and Maturity: Social Phobias, Anxiety Symptoms, Episodic Illusions and Idea of Reference

Abstract: In order to compare the prevalence of certain symptoms in adolescence with those at other ages, 6,034 apparently normal subjects aged 9–60 years were studied by questionnaire. Fear of blushing and fear of being looked at showed a maximum in the mid-teens and a subsequent gradual decrease both in males and females. They were more common in females at most ages. The anxiety symptoms also showed a peak in the mid-teens but there was a period of relative increase in the forties. Episodic illusions and the idea of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Reported anxiety reaches its lifetime peak in adolescence and intense and frequent negative affect also increases abruptly during this period (Abe & Suzuki, 1986; Steinberg, 2005). Neurobiological research suggests that adolescents experience an imbalance in the coupling of their subcortical emotional systems and cortical control regions, which can lead to heightened emotional reactivity especially in those with heightened genetic risk (Casey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Reported anxiety reaches its lifetime peak in adolescence and intense and frequent negative affect also increases abruptly during this period (Abe & Suzuki, 1986; Steinberg, 2005). Neurobiological research suggests that adolescents experience an imbalance in the coupling of their subcortical emotional systems and cortical control regions, which can lead to heightened emotional reactivity especially in those with heightened genetic risk (Casey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence may not only be a period of altered sensitivity to drugs of abuse, it also is a period of heightened levels of anxiety [47]. Studies in humans suggest that anxiety during adolescence may increase the risk for developing nicotine dependence [21,13,11].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, YRBS results showed that in the prior year, more than one in four adolescents (27.3%) had experienced significant symptoms of depression for at least two weeks, to the point that it interfered with their everyday functioning (Eaton, et al, 2008). Experiencing frequent negative affect is particularly common during the early adolescent years, more so in females than males (Larson, Moneta, Richards, & Wilson, 2002), and in addition to sad mood, also manifests itself in anxiety (Abe & Suzuki, 1986), self-consciousness, and low self-esteem (Simmons, Rosenberg, & Rosenberg, 1973; Thornburg & Jones, 1982). Feeling sad, depressed, or hopeless may be associated with the heightened rates of affective disorders, attempted and completed suicide, and addiction also observed during adolescence (Pine, Cohen, & Brook, 2001; Silveri, Tzilos, Pimentel, & Yurgelun-Todd, 2004; Steinberg, 2005, Mościcki, 2001).…”
Section: Storm and Stress? Affective Changes During Adolescencementioning
confidence: 99%